PROJECT-BASED LEARNING AND UNITY OF SCIENCE: ENHANCING THE CRITICAL THINKING OF STATE ISLAMIC UNIVERSITY STUDENTS - Fitriani, Amalia Dwi; Nasikhin (INTIHA: Islamic Education Journal, 2025)
This research aims to explore the implementation of Project Based Learning (PjBL) as a teaching method to foster students' critical thinking abilities at State Islamic University. The research method involved interviews with students and educators engaged in project-based learning. The findings indicated that Project Based Learning effectively cultivates students' critical thinking by providing practical experiences, team collaboration, and accountability for their education. The implications of this research highlight the importance of integrating Project Learning into the curriculum at State Islamic University to enhance students' critical thinking skills. It underscores educators' need for training and support to implement this teaching method effectively. Project Based Learning is academically relevant and significantly impacts students' social and professional advancement. Continuous development and adaptation of this approach prepare students to face real-world challenges with high levels of critical thinking and creativity. Implementing Project Learning also has the potential to enhance problem-solving skills, communication abilities, and high adaptability, all of which are highly required in today's job market. This study recommended that other educational institutions adopt the project-based learning method as part of their teaching strategies to produce globally competitive graduates.